2014
DOI: 10.1007/s11673-014-9549-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment for Vulvar Cancer for Indigenous Women From East Arnhem Land, Northern Territory: Bioethical Reflections

Abstract: This paper explores the bioethical issues associated with the diagnosis and treatment of vulvar cancer for Indigenous women in East Arnhem Land, Northern Territory, Australia. Based on a qualitative study of a vulvar cancer cluster of Indigenous women, the article highlights four main topics of bioethical concern drawn from the findings: informed consent, removal of body parts, pain management, and issues at the interface of Indigenous and Western health care. The article seeks to make a contribution towards I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Recent publications including the National Aboriginal and Torres Strait Islander Cancer Framework [25], The Optimal Care Pathway for Aboriginal and Torres Strait Islander people with cancer [26] and the Australian National Safety and Quality Health Service (NSQHS) Standards User guide for Aboriginal and Torres Strait Islander health [27] emphasise the importance of culturally safe, person-centred care and outline a number of areas to be considered when supporting the delivery of optimal care to Indigenous people. Despite these publications, many cancer providers and support services while committed to providing high quality care, often struggle with providing accessible, culturally safe cancer care to Indigenous Australians [24,28,29]. In the past decade, reports have begun to emerge of cancer services that provide innovative services to engage Indigenous patients and their families [30][31][32][33] although limited formal evaluation of successful cancer service delivery initiatives for Indigenous Australians have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications including the National Aboriginal and Torres Strait Islander Cancer Framework [25], The Optimal Care Pathway for Aboriginal and Torres Strait Islander people with cancer [26] and the Australian National Safety and Quality Health Service (NSQHS) Standards User guide for Aboriginal and Torres Strait Islander health [27] emphasise the importance of culturally safe, person-centred care and outline a number of areas to be considered when supporting the delivery of optimal care to Indigenous people. Despite these publications, many cancer providers and support services while committed to providing high quality care, often struggle with providing accessible, culturally safe cancer care to Indigenous Australians [24,28,29]. In the past decade, reports have begun to emerge of cancer services that provide innovative services to engage Indigenous patients and their families [30][31][32][33] although limited formal evaluation of successful cancer service delivery initiatives for Indigenous Australians have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicate studies, the titles and abstracts of 543 studies were screened, with 59 studies identified for full-text screening. Twenty-three qualitative studies [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the review after excluding quantitative studies ( n = 16), studies using the same dataset with different aims ( n = 3), studies not focused on Indigenous people’s experience with cancer ( n = 7), and studies not focused on Indigenous people with cancer ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…At least 145 participants (60%) were from regional/rural or disadvantaged areas. Ten studies had the same participants who shared their experiences in different healthcare service areas living in Northern Territory ( n = 3) [ 24 , 25 , 26 ], New South Wales ( n = 2) [ 29 , 38 ], and Western Australia ( n = 5) [ 33 , 34 , 35 , 36 , 39 ]. Most of the studies ( n = 21) conducted state-wide research; only two were conducted at the national level [ 21 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Providing cancer treatment services that meet the needs of Indigenous patients is a critical element in improving outcomes 23,24 . While evidence suggests that many mainstream cancer treatment centres and support services are currently failing to provide accessible, culturally appropriate cancer care to Indigenous Australians, 20,23,25–27 reports are starting to emerge of cancer services that are providing innovative services to engage Indigenous patients and their families 28–30 . However, there has been limited formal evaluation of such initiatives or the extent to which they occur in cancer services around Australia.…”
mentioning
confidence: 99%